Spinacopia dietkeyseri, a new species of Marine Ostracoda (Sarsiellidae: Myodocopina) from the Southern ocean - Chavtur, Vladimir G. (Zootaxa, 2016)
Spinacopia dietkeyseri, a new species of the family Sarsiellidae is described from the Southern Ocean (61°48.70’ S–47°28.04’ W to 61°48.57’ S–47°28.19 W) from the depth of 1993–1999 m. It very close to S. mastix Kornicker, 1975, but differs in the ornamentation on the surface of the carapace and in the number of setae on the maxilla, 5th, 6th and 7th limbs.